2014
DOI: 10.1021/jf405155p
|View full text |Cite
|
Sign up to set email alerts
|

Dry-Heating of Lysozyme Increases Its Activity against Escherichia coli Membranes

Abstract: For food as well as for medical applications, there is a growing interest in novel and natural antimicrobial molecules. Lysozyme is a promising candidate for the development of such molecules. This protein is largely studied and known for its muramidase activity against Gram-positive bacteria, but it also shows antimicrobial activity against Gram-negative bacteria, especially when previously modified. In this study, the activity of dry-heated lysozyme (DH-L) against Escherichia coli has been investigated and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Membrane permeabilization has been suggested as one of the mechanisms responsible for this activity [8,28]. This assumption was recently confirmed by our group who demonstrated that N-L causes the formation of pores and ion channels in the outer and cytoplasmic membranes, respectively [9,11]. Pore formation due to N-L implies that interactions occur between the protein and the E. coli outer membrane.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Membrane permeabilization has been suggested as one of the mechanisms responsible for this activity [8,28]. This assumption was recently confirmed by our group who demonstrated that N-L causes the formation of pores and ion channels in the outer and cytoplasmic membranes, respectively [9,11]. Pore formation due to N-L implies that interactions occur between the protein and the E. coli outer membrane.…”
Section: Discussionmentioning
confidence: 57%
“…Native lysozyme (N-L) has been shown active against Gram-negative bacteria such as E. coli [11,27]. Membrane permeabilization has been suggested as one of the mechanisms responsible for this activity [8,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations